Enhancing dielectric properties of ZnO nanopowders with 2D hBN doping: production, structural, morphological and dielectric characterization - Ozel, Cihan; Macit, Cevher Kursat; Gurgenc, Turan; Biryan, Fatih; Gurgenc, Ezgi; Bellucci, Stefano (Springer Heidelberg, 2024)
In this study, it was aimed to improve the dielectric properties of ZnO nanoparticles with the addition of hBN, which was not previously available in the literature, and thus to expand their usage areas. Sol-gel synthesis method was used in this study to create pure and hexagonal boron nitride (hBN) doped zinc oxide (ZnO) nanoparticles. Zinc acetate dihydrate Zn(CH3COO)22H2O), sodium hydroxide NaOH, and hexagonal boron nitride (hBN), all from Sigma Aldrich, were used as starting reagents. The reagents were dissolved during the sol-gel synthesis by being heated to 90 degrees C for 4 h in a magnetic stirrer. FT-IR, XRD, FE-SEM, EDX characterization techniques, and impedance analyzer were used to find functional groups, structural, morphological, and chemical composition, and dielectric properties of the nanoparticles, respectively. The produced un-doped and hBN-doped ZnO particles consist of nano-sized structures. Changes occurred in the intensities and locations of the XRD diffraction peaks and FT-IR peaks with the addition of hBN. Characteristic peaks of both ZnO and hBN were observed in the diffraction peaks of the doped nanoparticles. All nanoparticles were of high purity and were successfully produced by the sol-gel method. It was shown that as the hBN doping level increased, there were more hBN nanoplates in the ZnO matrix, and the EDX results also showed an increase in hBN addition. The frequency stability of the dielectric properties improved after hBN doping. While the dielectric constant at 1 kHz frequency at room temperature is 12.07 in pure ZnO nanoparticles, the increase up to 55.21 is observed in 10% hBN doped nanocomposites. This situation is considered as a great potential for technological applications of this novel nanocomposite material.
Keywords: Semiconductor; Nanomaterial; Ceramics; Zinc oxide; Hexagonal boron nitride; Dielectric